Legal characteristics of volunteers engaged in organizing and hosting sports events - M.N. Maleina (Ученые записки Казанского университета: Серия Гуманитарные науки)
Volunteering is a system of social relations. Taking into account the different schemes of legal relations, such volunteer movement participants as volunteer, voluntary organization, and benefitor have been defined. The paper substantiates the legal characteristics of sports volunteers: citizenship; voluntary, gratuitous, and personal character of their activity; its certain purposes; performing activities or providing services under the civil agreement or without it. The agreement on volunteer activity is concluded in practice and mentioned in legal acts, but its terms and responsibilities are not fixed. This agreement is either a civil contract for providing services or performing activities or a comprehensive contract. It has been suggested to amend the sports legislation due to a large number of participants in volunteer movements and persons in contact with them, as well as the need to maintain public safety and security of volunteers, interest of volunteers themselves in legal regulation of movement across the border of another state, guarantees of accommodation and workwear, taking into account their work as volunteers in the future, preserving the legal traditions in regulation of volunteer relations.